Analisis Minat Masyarakat terhadap Layanan Fintech Syariah: Studi Pengabdian Bersama BSI Gresik - Rachmaniyah, Fatichatur; Kusmayasari, Dewi; Khamila, Nabillatul; Astuti, Selvia Laely Dwi; Prameswana, Harda; Indriani, Arya Dhita (Jurnal Pemberdayaan Umat, 2025)
Purpose: This study aims to analyze public interest in Sharia fintech services, focusing on the collaborative community service initiative with Bank Syariah Indonesia (BSI) Gresik. This research seeks to identify factors influencing community adoption, perceptions, and challenges related to Sharia-compliant financial technology. Methodology/approach: The study was conducted in Gresik, East Java, in collaboration with BSI Gresik. Data were collected through surveys distributed to 150 respondents, including BSI customers and local residents. The survey utilized a structured questionnaire with Likert-scale questions covering aspects such as awareness, trust, and usage patterns of Sharia fintech. Results/findings: The findings indicate moderate awareness of Sharia fintech services, with trust in Islamic financial principles being a key driver of adoption. However, limited product knowledge and concerns regarding security were identified as barriers. Conclusion: The study concludes that while there is growing interest in Sharia fintech services, targeted educational campaigns and improved security measures are needed to boost adoption. Collaboration between Islamic banks and fintech providers can further enhance accessibility and trust, aligning with the principles of financial inclusion and compliance with Sharia. Limitations: The study was geographically limited to Gresik, and the sample may not fully represent diverse socioeconomic groups. Additionally, reliance on self-reported data may have introduced a bias. Contribution: This study contributes to the understanding of Sharia fintech adoption in Indonesia by providing insights for Islamic banks, fintech developers, and policymakers to enhance financial inclusion strategies. It also supports the academic discourse on Islamic finance and digital innovation.